2008
DOI: 10.1097/rli.0b013e318186531d
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Amide Substituent on the Biodistribution and Tolerance of Lanthanide(III) DOTA-Tetraamide Derivatives

Abstract: Objectives-Recent advances in the design of MRI contrast agents have rendered the lanthanide complexes of DOTA-tetraamide ligands of considerable interest, both as responsive MR agents and paramagnetic chemical exchange saturation transfer agents. The potential utility of these complexes for in vivo applications is contingent upon them being well tolerated by the body. The purpose of this study was to examine how the nature of the amide substituent, and in particular its charge, affected the fate of these chel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 45 publications
4
22
0
Order By: Relevance
“…complexes of LuL 1 , LuL 4 and LuL 8 (total [Lu 3+ ]: 0.1 mmolkg −1 ) showed signs of distress immediately post-injection and expired within 5 minutes. Given the slow rate of complex dissociation established both in vitro and in serum, death occurs too rapidly to be the result of dissociation of the complex and must be the result of an inherent toxicity of these tri-cationic complexes, consistent with our earlier report [8]. The cause of death was previously postulated to involve an interaction between the complex and heart tissue that caused a rapid weakening of the heart beat [8].…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…complexes of LuL 1 , LuL 4 and LuL 8 (total [Lu 3+ ]: 0.1 mmolkg −1 ) showed signs of distress immediately post-injection and expired within 5 minutes. Given the slow rate of complex dissociation established both in vitro and in serum, death occurs too rapidly to be the result of dissociation of the complex and must be the result of an inherent toxicity of these tri-cationic complexes, consistent with our earlier report [8]. The cause of death was previously postulated to involve an interaction between the complex and heart tissue that caused a rapid weakening of the heart beat [8].…”
Section: Resultssupporting
confidence: 82%
“…Such high doses can overwhelm transport pathways in the body, significantly altering the biodistribution profiles [21]. It has recently been reported that some tri-cationic DOTA-tetraamide complexes are acutely toxic in rodents at these high dose levels [8]. In order to assess the effect of this increased dose, injections of all five chelates were formulated with carrier added.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally the agent would adopt exclusively the conformation of the SAP isomer observed for S - SSSS -Eu 2 3+ . The chelates would need to be rendered both nontoxic (as these tricationic chelates are almost not well tolerated in vivo) [52] and made water-soluble; both of these prerequisites could be achieved through incorporation of three or four anionic groups, such as carboxylates, into the chelate structure [52]. …”
Section: Discussionmentioning
confidence: 99%
“…In the past 5 years (2007-2011), there have been 92 publications (of 552 or 17%) in Investigative Radiology that involved in a principal manner the gadolinium chelates. This included both basic research and clinical papers investigating new agents, [75][76][77][78][79][80][81][82][83][84][85][86][87][88] expanding the clinical applications for commonly used agents, 38,89 -123 assessing new imaging techniques, 124 -135 and evaluating the physicochemical properties and safety of these agents, 136 -148 focusing in particular on NSF. 46,73,74,149 -162 On the basis of target-specificity and clinical application of gadolinium agents, hepatobiliary contrast agents (Gd-BOPTA and Gd-EOB-DTPA) 89,92-96,98 -100,103-105,111,112,114,115,117-119,139 and blood pool agents (MS-325) 91,102,108 -110,116,121,123 constituted the emphasis of research involving MR contrast agents.…”
Section: Publications In Investigative Radiologymentioning
confidence: 99%